ANALISIS INVESTASI PADA PEMBANGUNAN PERUMAHAN JOGJA ECO WISATA - Aceng Kurniawan; Albani Musyafa (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Upala Villa Kedaton complex at Jogja Eco Wisata is meticulously designed to offer world-class comfort, featuring a Balinese home concept. Upala Villa Kedaton Jogja Eco Wisata is intended to become a new destination for shopping, education, culinary experiences, and recreation. The location is at Jl. Bulus II, Candibinangun, Pakem District, Sleman Regency, Special Region of Yogyakarta 55582. After collecting all the necessary data, it was organized and analyzed using various calculations according to standard formulas. These calculations included NPV (Net Present Value), IRR (Internal Rate of Return), BCR (Benefit Cost Ratio), PP (Payback Period), ROI (Return on Investment), and ROE (Return on Equity) to determine the project's feasibility. The analysis results yielded an NPV (Net Present Value) of 207.88 billion Rupiah. The IRR (Internal Rate of Return) was 30.11%, which is higher than the MARR (Minimum Attractive Rate of Return) of 15%. The BCR (Benefit Cost Ratio) was 1.2584, indicating that the ratio of income to expenditure is greater than 1, making it viable. The Payback Period was calculated to be 1.017 years, or approximately 12.2 months, or 366 days, meaning investors can expect to recover their money in that timeframe. The Return on Investment was 15.32%, and the Return on Equity was 39.65%. From these calculations, we can conclude that the Upala Villa Kedaton Jogja Eco Wisata housing project is a viable investment. This conclusion is based on the positive NPV of 207.88 billion Rupiah, an IRR of 30.11% which is higher than the initial MARR of 15%, a Benefit Cost Ratio of more than 1 at 1.2584, a Return on Investment of 15.32%, and a Return on Equity of 39.65%.